Meningkatkan Hasil Belajar IPA Siswa Melalui Pembelajaran Kooperatif Tipe Time Token Pada Materi Cahaya Di Kelas VIII C Sekolah Menengah Pertama Negeri 7 Batanghari - Desma Yetti; journal journal (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: The purpose of this study is to improve students’ learningresult in science studies, especially lighting subject through timetoken learning model in for students di kelas VIIICSMP N 7Batanghari 2016/2017 academic year. This study employ classaction research in three cycles. The data collected throughobservation, documentation and interview. The subject of this studywas students in class VIIICsemester II SMP N 7 Batanghari2016/2017 academic year. The result of study shows that the timetoken learning model in science studies is able to improve studentslearning result in lighting subject. It can be seen from theresultsfrom cycle I to Cycle III (cycle I: 6.50; cycle II: 7.27; cycleIII: 8.36.